PENGARUH PROMOSI MEDIA SOSIAL DAN HARGA PADA KEPUASAN KONSUMEN DI MERDEKA CAFE NGANJUK - Novaliana, Ika (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2021)
Promotion through social media are carried out by companies to introduce products to consumers, besides that’s companies must consider price because it will affect consumers in making purchases which can determine consumer satisfaction. The purpose of this study was to determine the effect of social media promotion and price on consumer satisfaction at Merdeka Cafe Nganjuk. This study uses quantitative methods with a sample of 80 respondents. Collecting data through observation, interviews and questionnaires. The data analysis technique used was multiple linier regression analysis. The results showed that partially social media promotion had an effect on consumer satisfaction and price had an effect consumer satisfaction, while simultaneously social media promotion and price had an effect on consumer satisfaction.